2021
DOI: 10.1002/acm2.13167
|View full text |Cite
|
Sign up to set email alerts
|

Vendor‐independent skin dose mapping application for interventional radiology and cardiology

Abstract: Purpose The purpose of this paper is to present and validate an originally developed application SkinCare used for skin dose mapping in interventional procedures, which are associated with relatively high radiation doses to the patient’s skin and possible skin reactions. Methods SkinCare is an application tool for generating skin dose maps following interventional radiology and cardiology procedures using the realistic 3D patient models. Skin dose is calculated using data from Digital Imaging and Communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The comparison between PyMCGPU-IR and the experimental set-ups PA, PALAO and PALAOCRA show very good agreement in the calculation of the peak skin dose, with differences below 6 %. In a recent article [24], Krajinovic et al presented and validated the SkinCare application (Open Source). For validation purposes, among other tests, they used a similar set-up to measure skin dose and reported that the doses calculated by SkinCare were within 16.9 % of the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between PyMCGPU-IR and the experimental set-ups PA, PALAO and PALAOCRA show very good agreement in the calculation of the peak skin dose, with differences below 6 %. In a recent article [24], Krajinovic et al presented and validated the SkinCare application (Open Source). For validation purposes, among other tests, they used a similar set-up to measure skin dose and reported that the doses calculated by SkinCare were within 16.9 % of the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]10,12,16 A calibration curve is necessary to evaluate the response of the film as a function of film exposure since their response is not linear with the dose. 17,18 This study used the calibration curve that was established in the framework of the European project VERIDIC 8,11,12,19 that started in 2018 and mainly aimed to review and validate existing PSD software products on phantom conditions. GafChromic XR-RV3 films calibration was performed at the national metrology laboratory for ionizing radiation (LNHB, PARIS, FRANCE).…”
Section: Skin Dose Measurementsmentioning
confidence: 99%
“…Although the assessment of the PSD can be performed with a wide choice of detectors, 3 the use of software tools is more practical and economical. Different commercial skin dose mapping software packages have been developed to estimate the skin dose delivered to the patient during or after the IR procedure (for instance, Dose Tracking System (Canon Medical Systems), 4 DoseMap (GE Healthcare), 5,6 NEXO[dose] (BRACCO), 7 Radimetrics (Bayer), 8 DOSE (Qaelum), 9 Radiation Dose Monitor (Medsquare) 10 ). These software tools estimate the PSD using the dosimetry indicators and geometry information collected during the IR procedure.…”
Section: Introductionmentioning
confidence: 99%